Training for Improving Competence of Senior High School Geography Teachers in Remote Sensing at Sman 16 Padang City - Putri, Sri Kandi; Chandra, Deded; Edial, Helfia; Mariya, Sri; Pertiwi, Mentari Dian; Nova, Sari (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
This article aims to enhance the capabilities of teachers and students in the field of Remote Sensing and to understand the components present in remote sensing products. This activity took place at SMAN 16 Padang using a training and question-and-answer method. Participants included geography teachers and students, with 20 participants representing each class. Despite the lifting of the PPKM policy by the President, it is important to always adhere to the applicable protocols and implement all previously registered regulations. The activities included training related to Remote Sensing and the process of creating remote sensing products for geography teachers and students. Through this training, participants experienced an improvement in understanding or the ability to comprehend various aspects of the remote sensing product creation process. Geography teachers also gained a better understanding of the necessary competencies in designing and utilizing remote sensing products, thus promoting quality and effective learning.